Thomas Aquinas : faith, reason, and following Christ - Bauerschmidt, Frederick Christian (Christian theology in context., 2013)
An introduction to the thought of Thomas Aquinas (1225-1274) who is one of the most significant Christian writers of the Middle Ages. It pays particular attention to the Aquinas's context as a Dominican friar, devoted to the task of preaching the Christian gospel.